(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
Olive fruit fly is the most harmful pest in olive fruit and oil production. Damages involve yield reduction as a consequence of premature fruit drop, but also reduced quality of olive oil and olive products. In Montenegro, little data is available on biology of Bactrocera oleae. Knowledge on developmental cycle of this pest would improve optimization of insecticide application timing and therefore the protection of fruits, and would consequently reduce adverse effects on the environment. Investigations were conducted in olive grove located in Bar, on Žutica variety, during three-year period. Population dynamics of pre-imaginal stages and fruit infestation level were monitored from the middle of July until the end of October. The beginning of infestation in all three investigation years was at the end of July. Until the end of August, depending on environmental conditions, the infestation was low. In September and October it multiplied and reached maximum by the end of October. In infestation structure, until the middle of September eggs and larvae (L1) were dominant. From the middle of September until the middle of October the presence of all developmental stages (eggs, larvae, pupae) of the pest was equal in fruits. In the following period, pupae, coccons and abandoned galleries prevailed.